2022
DOI: 10.7554/elife.77266
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar energy costs across the tree of life

Abstract: Flagellar-driven motility grants unicellular organisms the ability to gather more food and avoid predators, but the energetic costs of construction and operation of flagella are considerable. Paths of flagellar evolution depend on the deviations between fitness gains and energy costs. Using structural data available for all three major flagellar types (bacterial, archaeal, and eukaryotic), flagellar construction costs were determined for Escherichia coli, Pyrococcus furiosus, and Chlamydomonas reinhardtii. Est… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 93 publications
0
35
0
Order By: Relevance
“…The flagellum is an important structure for the initial step of bacterial pathogenesis, enabling motility of the bacterium and allowing it to migrate, attach and colonize host cells as well as enabling its survival [ 39 ]. Moreover, flagella promote the uptake of essential nutrients, and as a result, has a critical role in the virulence of pathogenic organisms [ 40 ]. Transcriptomic analysis revealed that hydroquinine treatment of P. aeruginosa ATCC 27853 significantly downregulated 8 flagella-related genes, encoding the flagellar assembly of hook–filament junction ( flgK ), hook modification protein ( flgD ), basal body-associated proteins ( flgB , flgC , flgH , flgJ , fliF ) and motor-switch protein ( fliG ) ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The flagellum is an important structure for the initial step of bacterial pathogenesis, enabling motility of the bacterium and allowing it to migrate, attach and colonize host cells as well as enabling its survival [ 39 ]. Moreover, flagella promote the uptake of essential nutrients, and as a result, has a critical role in the virulence of pathogenic organisms [ 40 ]. Transcriptomic analysis revealed that hydroquinine treatment of P. aeruginosa ATCC 27853 significantly downregulated 8 flagella-related genes, encoding the flagellar assembly of hook–filament junction ( flgK ), hook modification protein ( flgD ), basal body-associated proteins ( flgB , flgC , flgH , flgJ , fliF ) and motor-switch protein ( fliG ) ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epistasis and functional redundancy in biochemical pathways impede the accurate forecasting of mutagenic events responsible for rescuing a phenotype, which could be the result of loss-of-function mutations in negative regulators or gain-of-function mutations in positive regulators ( 28 ). The flagellar system and its regulatory elements have been known to be under selective pressure due to their associated energetic and fitness costs, not only always resulting in positive selection but also often resulting in gene deletion or inactivation by insertion sequences ( 29 34 ). By targeting the stator subunit of the flagellar motor, we have been able to study the molecular events leading to the spontaneous adaptation of a unique module within a highly conserved molecular complex ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Motility confers a fitness advantage that is worth significant energetic investment despite the high cost of synthesizing the flagellar machinery ( 5 , 34 , 64 ). This advantage can only be seized if the correct ions are available for stator conversion into torque.…”
Section: Discussionmentioning
confidence: 99%
“…The buildup and operation of flagella is estimated to use 5 to 10% of the total cell energy budget ( 69 , 70 ) and, hence, confers a substantial cost for Salmonella growth. It is therefore possible that the decreased persister levels in the Δ flhDC mutant ( Fig.…”
Section: Resultsmentioning
confidence: 99%